Opioid epidemic: why replacement therapy is part of the answer - Asma Suleman; Anees Fatima; Ali Madeeh Hashmi (Journal of the Pakistan Medical Association, 2025)
Globally, about 4.7% or 184 million people aged between 15 and 64 are found to indulge in the consumption of illegal drugs annually, with an alarming increment in these statistics.1 Notably, Pakistan tops the charts for the highest per capita heroin consumption across the globe,2 and the Province of Punjab experiences significant challenges due to its strategic location on a major drug trafficking route, primarily because of opium poppy and cannabis cultivation in the adjacent country, Afghanistan.3 Unsafe injection practices among individuals struggling with opioid addiction pose significant risks for contracting HIV and hepatitis.4 Sharing needles or using unclean equipment can facilitate the transmission of bloodborne viruses such as HIV and hepatitis B and C. The presence of these viruses in contaminated needles or injection paraphernalia can easily spread among users, creating a vicious cycle of infection within communities affected by opioid addiction. Moreover, the impairing effects of opioids can diminish judgment and decision-making abilities, leading individuals to engage in risky behaviours without considering the potential consequences.5 This not only endangers the health of the individuals directly involved but also contributes to the broader public health burden of infectious diseases. To mitigate these risks, harm reduction strategies such as needle exchange programmes and access to clean injection equipment are crucial, alongside comprehensive addiction treatment and education efforts. Despite the growing opioid crisis in Pakistan, the current response is insufficient. The government’s primary approach involves mandatory detention of individuals with OUD at state-run rehabilitation centers. For this purpose, in the Punjab Province, 10 drug treatment facilities have been established,5 yet none offer medication-assisted opioid substitution therapy. Instead, the focus remains on managing withdrawal symptoms or the detoxification phase, culminating in 15-day detentions. However, research suggests that such detention measures are rarely successful, as evidenced by high relapse rates among treated individuals.6 —Continue